APPLICATION OF THE RECHTERLIJK PARDON PRINCIPLE IN CRIMINAL CASE DECISIONS WITHIN THE REFORM OF NATIONAL CRIMINAL LAW - Erdiansyah; Ellydar Chaidir; Heni Susanti (Proceeding International Conference on Social Sciences, 2026)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP) introduces significant reforms to the national criminal law system, one of which is the incorporation of the rechterlijk pardon principle. This principle grants judges the authority not to impose punishment on defendants proven guilty of minor offenses, taking into account considerations of justice and humanity. This study analyzes three key issues: (1) the application of the rechterlijk pardon principle in current criminal case decisions and its future implementation under the new Criminal Code; (2) the strengths and weaknesses of implementing the rechterlijk pardon principle in criminal case decisions. The research employs a normative legal method with a statutory approach, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The findings reveal that the rechterlijk pardon principle is not recognized in the current Dutch-derived KUHP, thereby providing no legal room for judges to pardon defendants in minor cases. The new KUHP, through Article 54 paragraph (2), introduces a significant reform by granting judges the discretion not to impose punishment in the interest of justice and humanity. Although newly codified, the practice of judicial pardon has long existed in the Netherlands and has begun to appear in several Indonesian court decisions. The weaknesses of its implementation include the lack of synchronization between the KUHP and the Criminal Procedure Code (KUHAP), while its strengths lie in sentencing flexibility, recognition of behavioral reform, reduction of prison overcrowding, and enhancement of a more humane justice system